Comprehensive profile of circRNAs in formaldehyde induced heart development. (April 2022) - Zhang, Ying; Yang, Yanyan; Ju, Hui; He, Xiangqin; Sun, Pin; Tian, Yu; Yang, Panyu; Song, Xiao-xia; Yu, Tao; Jiang, Zhirong
Abstract: Circular RNAs (circRNAs) are a novel type of long non-coding RNAs that can regulate gene expression in heart development and heart disease. However, the expression pattern of circRNAs in congenital heart disease (CHD) induced by formaldehyde exposure is still unknown. We detected circRNAs expression profiles in heart tissue taken from six neonatal rat pups with formaldehyde exposure group and normal group using RNA-sequencing. Results revealed that a total of 54 circRNAs were dysregulated in the formaldehyde exposure group compared to the normal group. Among them, 31 were upregulated and 23 were downregulated (fold change = 2.0, p < 0.0 5). The qRT-qPCR results showed that expressions of 12:628708|632694, 18:77477060|77520779, 5:167486001|167526275 were significantly upregulated, while that of 7:41167312|4116775 and 20:50659751|5068786 were notably downregulated; the expression pattern was consistent with the RNA sequencing data. Bioinformatics analysis shows that the pathogenesis of formaldehyde exposure-induced CHD may involve Hippo-YAP pathway、Notch signaling pathway and other pathways. A key miRNA (rno-miR-665) was identified by constructing a circRNA-miRNA-mRNA co-expression network. In summary, the study illustrated that circRNAs differentially expressed in fetal heart tissues during formaldehyde exposure has potential biological functions and may be a biomarker or therapeutic target for CHD.